2015 IEEE First International Conference on DC Microgrids (ICDCM) 2015
DOI: 10.1109/icdcm.2015.7152031
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of DC and AC microgrids in commercial buildings across different climates and operating profiles

Abstract: Bosch has developed and demonstrated a novel direct current (DC) microgrid system that maximizes the efficiency of locally generated photovoltaic energy while offering high reliability, safety, redundancy, and reduced cost compared to equivalent alternating current (AC) systems. Several demonstration projects validating the system feasibility and expected efficiency gains have been completed and additional ones are in progress. This paper gives an overview of the Bosch DC microgrid system and presents key resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
68
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
3

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(81 citation statements)
references
References 2 publications
0
68
0
2
Order By: Relevance
“…A highlight of the Bosch DC power system configuration is that maximum power point tracking (MPPT) is not performed directly after the PV array, but rather at the AC/DC gateway converter, allowing for higher system efficiency. (Fregosi et al 2015) Eindhoven HTC Netherlands Philips has implemented a grid-connected, PV-powered DC test bed installation for an office LED lighting system at the Eindhoven (Netherlands) High Tech Campus, and compared its energy performance against an equivalent AC system. The site has demonstrated 2% electricity savings and 5% potential savings for the DC system.…”
Section: And Dc/ac Hybrid Zne Building Microgrid Systemsmentioning
confidence: 99%
“…A highlight of the Bosch DC power system configuration is that maximum power point tracking (MPPT) is not performed directly after the PV array, but rather at the AC/DC gateway converter, allowing for higher system efficiency. (Fregosi et al 2015) Eindhoven HTC Netherlands Philips has implemented a grid-connected, PV-powered DC test bed installation for an office LED lighting system at the Eindhoven (Netherlands) High Tech Campus, and compared its energy performance against an equivalent AC system. The site has demonstrated 2% electricity savings and 5% potential savings for the DC system.…”
Section: And Dc/ac Hybrid Zne Building Microgrid Systemsmentioning
confidence: 99%
“…The AC/DC converter performs the voltage regulation of the DC bus voltage according to a maximum power point tracking (MPPT) algorithm for the PV generator. In contrast with the conventional microgrid configuration, the MPPT converter, is not in the path from PV to load, which enables higher efficiency and higer reliability than systems using a dedicated MPPT converter [21]. The analysis showed that the system can improved PV energy utilization up to 8%.…”
Section: Variable DC Bus Voltage Distribution Systemsmentioning
confidence: 99%
“…However, load variation was not considered for this study. The authors of [21] discussed the comparison of AC and DC systems with the inclusion of solar PV. They concluded that the DC system utilized solar energy was better than the AC system.…”
Section: Introductionmentioning
confidence: 99%